A short history of the american revolutionary war - Conway, Stephen (London : I. B. Tauris, 2013)
The American war against British imperial rule (1775-1783) was the world's first great popular revolution. Ideologically defined by the colonists' formal Declaration of Independence in 1776, the struggle has taken on something a mythic character, especially in the United States. From the Boston Tea Party to Paul Revere's ride to raise the countryside of New England against the march of the Redcoats; from the heroic resistance of the militia Minutemen at the battles of Lexington and Concord to the famous crossing of the Delaware by General George Washington; and from the American travails of Bunker Hill (1775) to the final humiliation of the British at Yorktown (1781), the entire contest is now emblematic of American national identity. Stephen Conway shows that, beyond mythology, this was more than just a local conflict: rather a titanic struggle between France and Britain. The thirteen colonies were merely one frontline of an extended theatre of operations, with each superpower aiming to deliver the knockout blow. This bold new history recognizes the war as the Revolution but situates it on the wider, global canvas of European warfare.